British authors published abroad - Stevenson, J (Wiley, 2017)
My present work is a study of British authors published abroad. In the seventeenth century, English and Scots had a negligible readership outside the British Isles. The principal languages of Europe were Latin, the language of the clerisy and of scientific exchange, and French, the language of chivalry and diplomacy. It follows that British authors could make an impression abroad only if they wrote in Latin or if their work underwent translation. The quantity and significance of the resultant literature is little understood. Additionally, because there is so little translation of literary texts, the importance of translation out of English is often underestimated. A huge amount of political and theological writing was published in Dutch translation: There is also an important phenomenon of “onward translation” from Dutch to German, and from German to the Scandinavian languages, Polish, and other tongues, without reference to the original English texts (there is also a smaller, but significant “onward” process from French to other romance languages). The Elizabethan puritans in particular have a major presence in Continental translation. There is also a political dimension to publication abroad: The English state attempted to remedy propaganda disasters by having recourse to foreign presses, and dissident writers attempted to sway opinion both at home and abroad. Furthermore, significant quantities of writing were produced within diaspora communities; the most salient being the separatist Protestant churches in the Netherlands that included the Pilgrim Fathers, and the Catholic seminaries and monasteries. Many of these had well‐developed networks of international communication.